Development Of Adobe Captivate-Based Arabic Reading Skill Learning Media For Students Of Class X SMA - Adam Ghozali Reynaldo Suharto (Institut Agama Islam An-Nawawi Purworejo, 2023)
Many students experience difficulties in reading Arabic texts in several schools due to the lack of variety of learning media applied in class. This study aims to develop IQRA (Interactive Quiz for Reading in Arabic), an Adobe Captivate-based learning media for the Arabic reading skills of class X high school students. The method used in this research is research and development. The development design used to design this media refers to ADDIE. The research data was obtained using the nontest technique. The non-test instruments used were interviews, observations, teacher and student needs questionnaires, expert validity test questionnaires, product satisfaction questionnaires, and SWOT questionnaires for old and new products. The result of this study is an Adobe Captivate-based media prototype for the Arabic reading skills of class X high school students in the form of a Windows application (.exe). Based on a questionnaire that analyzes the needs of teachers and students, this Adobe Captivate-based media contains 3 themes, namely البيانات الشخصية, المرافق العامة في المدرسة, الحياة في الأسرة وفي السكن. The assessment of experts and teachers is that this Adobe Captivate-based media is appropriate in the aspects of software engineering, audio aspects, and visual aspects. The implementation of this media is a product satisfaction questionnaire by experts and practitioners who are declared appropriate. While the evaluation of this media is by SWOT analysis of old products by teachers and students, as well as SWOT analysis of new products by teachers and experts.